Effects of BEST in CLASS–Web on Teacher Outcomes: A Preliminary Investigation. (June 2022) - Conroy, Maureen A.; Sutherland, Kevin S.; Granger, Kristen L.; Marcoulides, Katerina M.; Feil, Edward; Wright, Jessica; Ramos, Mayra; Montesion, Alexandra
This study examined the effects of the BEST in CLASS intervention professional development component when delivered online in comparison with in person and a control group. A total of 29 early childhood teachers serving young children demonstrating challenging behaviors were included as participants. Data were collected on teachers' classroom quality, self-efficacy, implementation of the BEST in CLASS practices, acceptability of the intervention, and costs of delivery. Positive outcomes on several dimensions of classroom quality were found for the BEST in CLASS–Web condition when compared with the BEST in CLASS and control conditions. Alternatively, teachers' sense of self-efficacy was greater when BEST in CLASS was delivered in person when compared with teachers who received online delivery or those in the control condition. Finally, teachers in both treatment conditions increased their use of the practices in comparison with control teachers. Teachers in both treatment conditions rated BEST in CLASS with high levels of acceptability. Implications and future research directions are discussed.